Fatty acids as dietary tracers in integrated production of fish/oysters/macroalgae in earthen ponds - Brito, Gonçalo Cardoso de Menezes Villa de (2017)
Semi-intensive fish culture developed in earthen ponds is the main type of production system used nowadays in Portugal. One way to decrease its environmental footprint, by reducing waste effluents, is to integrate the production of organic and inorganic extractive species such as bivalves and seaweeds directly in the ponds, under the principles of IMTA. Furthermore, the total biomass of product at one site is increased and diversification of products is accomplished, promoting higher profitability. There are needs for integrated knowledge concerning the efficiency of nutrient use, such as fatty acids. The present study refers to a pond where the only input was the feed, for the culture of three fish species (Argyrosomus regius, Diplodus sargus, Mugil cephalus) along with oysters (Crassostrea gigas) and sea lettuce (Ulva flexuosa). Additionally, natural occurring organisms in the ponds were sampled, such as phytoplankton, suspended particulate organic matter, zooplankton, polychaetas and other two macroalgal species, Ulva intestinalis and Rhizoclonium riparium. The main objective of the work was to identify food sources used by heterotrophic species present in the ponds using fatty acids as trophic markers. Three configurations (treatments) were tested, one comprised only the culture of fish and oysters, another comprised only fish and algae, while the last comprised all species cultured together. Profiles from each heterotrophic species across treatments were compared, and their differences evaluated to identify possible variations in feeding sources across treatments. Polychaetes showed dietary tracers of the commercial feed, macroalgae, sediment and additionally is suggested the ability to biosynthesize C20:2ω6 from Linoleic Acid. In zooplankton, the dietary tracers found reflect a consumption of phytoplankton, suspended matter and bacteria, while the higher levels of DHA and EPA could be linked with a higher accumulation of PUFA with decreasing temperatures. Oysters reflected trophic markers of phytoplankton, ...